1986
DOI: 10.1287/mksc.5.4.325
|View full text |Cite
|
Sign up to set email alerts
|

A Probabilistic Model for the Multidimensional Scaling of Proximity and Preference Data

Abstract: A probabilistic multidimensional scaling model that estimates both location and variance parameters for proximity and preference data is described and compared to a deterministic scaling model. Simulated and empirical choice data are used to compare models. Variance estimates from the probabilistic model are used to test a hypothesis about the homogeneity of stimulus perception under alternative modes of stimulus presentation.probabilistic model, preference data, proximity data, multidimensional scaling

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 28 publications
0
32
0
1
Order By: Relevance
“…Market analysis, in this context, involves understanding customers' perceptions, analyzing the nature of competition, and identifying market opportunities. An increasingly sophisticated number of algorithms for analyzing proximity data with the use of both spatial and tree-based techniques have emerged over the years to handle problems ranging from individual differences, to asymmetric data, to uncertainty (DeSarbo, Johnson, Manrai, Manrai, & Edwards 1992;DeSarbo & Rao, 1984;MacKay & Zinnes, 1986). There are also hybrid techniques, which simultaneously represent proximities with the use of both types of structures (Carroll, 1976;Shepard, 1980).…”
Section: Spatial and Tree-based Similarity Scalingmentioning
confidence: 99%
“…Market analysis, in this context, involves understanding customers' perceptions, analyzing the nature of competition, and identifying market opportunities. An increasingly sophisticated number of algorithms for analyzing proximity data with the use of both spatial and tree-based techniques have emerged over the years to handle problems ranging from individual differences, to asymmetric data, to uncertainty (DeSarbo, Johnson, Manrai, Manrai, & Edwards 1992;DeSarbo & Rao, 1984;MacKay & Zinnes, 1986). There are also hybrid techniques, which simultaneously represent proximities with the use of both types of structures (Carroll, 1976;Shepard, 1980).…”
Section: Spatial and Tree-based Similarity Scalingmentioning
confidence: 99%
“…Theoretical and empirical comparisons of probabilistic MDS models have shown that they provide results that are often equal or better than those of deterministic MDS models (MacKay 1983; MacKay andZinnes 1981, 1986).…”
Section: Spatial Variation Estimation In Geography and Surveyingmentioning
confidence: 99%
“…In the spatial behavior literature, cognitive maps have been estimated using a variety of methods which include sketch maps (Buttenfield 1986;Lynch 1960;Wood and Beck 1989), direct numerical estimation of coordinates (MacKay and Zinnes 1981;Muller 1985), MDS (Golledge 1978;MacKay and Zinnes 19811, map boards (Richardson 1981;Sherman, Croxton, and Giovanatto 19791, and point estimation on a CRT or digitizer (Baird 1979;Lloyd 1989).…”
Section: Spatial Variation Estimation In Geography and Surveyingmentioning
confidence: 99%
“…Maximum likelihood MDS methods have been developed by Ramsay (1982), Takane (1982), MacKay (1989) and MacKay and Zinnes (1986), among others. Least squares MDS methods have been proposed by DeLeeuw and Heiser (1982), Heiser and Groenen (1997), Groenen (1993), and Groenen, Mathar, and Heiser (1995) among others.…”
Section: Introductionmentioning
confidence: 99%